Optoelectronic enhancement of ZnO/p-Si Schottky barrier photodiodes by (Sn,Ti) co-doping - Mensah-Darkwa, Kwado; Ocaya, Richard O.; Al-Sehemi, Abdullah G.; Yeboah, Daniel; Dere, Aysegul; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier, 2023)
In this study, metal-semiconductor-metal (MSM) ZnO-based Schottky barrier diodes (SBDs) were fabricated on the basis of titanium-doped tin-zinc oxide (SZT) films by sol-gel spin coating. Au/(Sn:Zn):Ti:ZnO/p-Si/Au SBDs with varying wt% of Ti were then fabricated. The effects of Ti doping concentration on the structural, optical, and electrical properties were studied. The doped films are consistently homogeneous with increasing Ti content. The optical measurements confirm high film transmittance in the visible spectrum. The optical band gap energy of the SZT films was around 3.90 & PLUSMN; 0.02 eV. The current-voltage, impedance spectroscopic, and photoresponse measurements showed that Ti-doping improved the performance of the devices by increasing the barrier heights and hence the rectification ratios of the devices. The reduction in ideality factors and series resistances implies that Ti doping improves the devices towards near-ideal behavior by passivating interface states.
Keywords: Ideality factor; Schottky barrier height; Transition metal co-doping; Oxidation state doping